Sur la corde raide : rente pétrolière et développement en Équateur (1972-2017) - Constantin Lopez (Revue de la Régulation)
This article deals with the conditions of oil rent management in Ecuador during the oil era (1972-2017) from an historical and institutional perspective. We distinguish three periods: oil nationalism (1972-1981), neoliberalism (1982-2006) and the Citizens’ Revolution (2007-2017. The first part discusses the issues related to the management of rent in a dependent, commodity-exporting economy. A second part considers the stress associated with rent management between 1972 and 2006. At that time, a political coalition led by financial / agro-exporting oligarchs and US capitalists hampered state modernization and favored inefficient management of oil rents, which exacerbated the country’s dependence. In a third part, we show that from 2007, the Citizens’ Revolution implemented new methods of rent management in a favorable context, however, it had limited room for maneuver in terms of economic policy.